Choice and Opportunity Costs - Manzini, Paola; Mariotti, Marco; Ülkü, Levent (Review of Economic Studies, 2025)
Abstract We define the (physical) opportunity cost of a choice x as the alternative that would be chosen if x were not available, and the opportunity cost of any unchosen alternative as x itself. The agent has preferences over pairs consisting of alternatives and their opportunity costs. Because costs affect choice and vice-versa, choice results from an intrapersonal equilibrium rather than from simple maximisation. In spite of significant rationality assumptions, the resulting behaviour can be highly non-standard, allowing intransitive choices. Rational utility maximisation is ensured by an additional new consistency condition on preferences. However, we argue that the maximised utility cannot be straightforwardly interpreted as a welfare relevant “revealed preference”. A generalisation of our model accommodates additional departures from standard rationality in the form of menu effects.